2014
DOI: 10.3109/01913123.2014.937842
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Satellite Cells in Amyotrophic Lateral Sclerosis

Abstract: Our data suggest that the capacity of ALS SCs to proceed through the myogenic program seems to be altered: SCs seem to lose their ability to regenerate and restore mature myofibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 17 publications
7
52
1
Order By: Relevance
“…Most importantly, satellite cells isolated from presymptomatic animals exhibited less proliferative capacity in vitro than satellite cells isolated from wild-type littermates (73). This diminished capacity to develop normally was also observed in satellite cells derived from ALS patients (94,103). As these cells neither contract nor receive direct motor neuronal input, it is speculated that their modifications could attest at least in part to an intrinsic muscle pathology.…”
Section: Motor Neurons or Myofibers: Who Are First?mentioning
confidence: 96%
“…Most importantly, satellite cells isolated from presymptomatic animals exhibited less proliferative capacity in vitro than satellite cells isolated from wild-type littermates (73). This diminished capacity to develop normally was also observed in satellite cells derived from ALS patients (94,103). As these cells neither contract nor receive direct motor neuronal input, it is speculated that their modifications could attest at least in part to an intrinsic muscle pathology.…”
Section: Motor Neurons or Myofibers: Who Are First?mentioning
confidence: 96%
“…; Scaramozza et al. ). However, whether skeletal muscle satellite cell differentiation is affected by spinal cord injury in humans remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…; Scaramozza et al. ). Thus, primary human skeletal muscle cultures have provided meaningful insight into satellite cell function in muscle disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the exclusive expression of mutant SOD1G93A (mSOD1) in the skeletal muscles can lead to denervation of the neuromuscular junctions (NMJs), which lose the ability to regenerate and become atrophic, thus contributing to the symptoms of ALS . Indeed, several mechanisms implicated in the physiological maintenance of skeletal muscle are deregulated in ALS, such as satellite cell (SC) activity, mitochondrial and miRNA biogenesis . It is interesting that these processes act synergistically to maintain healthy skeletal muscle, and influence both the number and the activity of the innervated junctions .…”
Section: Introductionmentioning
confidence: 99%